RELIGIOUS FUNDAMENTALISM: PSYCHOLOGICAL FACTORS - Jose Thadavanal CMI (Journal of Dharma, 1990)
On February 14, 1989, Ayatollah Ruhollah. Khomeini, the spiritual leader of the Moslems in Iran, announced the following to the world Moslem community: "would like to inform all the fearless Moslems in the world that the author of the book entitled The Satanic Verses, ... as well as the publishers, •.. have been sentenced to death. I call on all zealous Moslems to execute them quickly, wherever they find them.... ", "Whoever is killed on this path," continued the Ayatollah, "will be regarded as a martyr."! As a committed Moslem, Khomeini is convinced that both the Christian West and the Jewish State are pawns in the hands of the Devil for the destruction of Islam. Hence his propaganda machine portrays the U.S. as ’the great Satan’ and Zionism (alias the Jews) which had been at work ’for centuries everywhere, perpetrating crimes of un- believable magnitude against human societies and values’, asanemanation of Satan.t As Paul Johnson remarks, ’Khornelnl followed the medieval line that Jews were subhuman or inhuman, indeed antihuman, and there- fore constituted an interminable category of creeture’.> Khomeini ’found it difficult to decide whether Satan was manipulating Washington via the Jews or vice versa’.In his own country, Khomeini ’succeeded’ in making a quarter million of his people ’martyrs’ for Islam. Khomeini knew how to use the ’weapon’ of Islam even against an Islamic country. Hepresented President Saddam Hussein of Iraq as an ’infidel’ who dared wage a war against the government of God and Islam. Therefore, to fight until the overthrow of Saddam Hussein is a religious duty of all Moslems. Those who perish in the war die for Islam and therefore are all martyrs.